SYSTEMATIC LITERATURE REVIEW: HEALTHCARE HUMAN RESOURCE RETENTION STRATEGIES IN REDUCING TURNOVER IN HOSPITALS - Dea Erica; Adhietya Widyaningrum; Indri Lestari; Audrianto; Radyta Radwa Maudyna; Vip Paramarta (CV. Radja Publika, 2026)
The high turnover rate of healthcare personnel in hospitals has become a major challenge in human resource management, as it can disrupt service continuity, reduce the quality of healthcare services, and increase recruitment and training costs for new employees. Therefore, effective retention strategies are essential to retain competent healthcare professionals and ensure the sustainability of hospital services. This study aims to identify the factors contributing to healthcare workforce turnover and to analyze human resource retention strategies for reducing turnover in hospital settings. The study employed a Systematic Literature Review (SLR) approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 20 scientific articles, consisting of 10 national and 10 international journals published between 2020 and 2026, were selected based on predetermined inclusion and exclusion criteria. The selected studies were analyzed descriptively through the processes of identification, screening, evaluation, and synthesis of research findings. The results indicate that the primary factors contributing to turnover include excessive workload, burnout, inadequate compensation, ineffective leadership, low job satisfaction, organizational culture, work-life balance, employee engagement, and limited career development opportunities. The most frequently recommended retention strategies include fair compensation and reward systems, career development, continuous training, mentoring programs, transformational leadership, strengthened organizational support, a positive work environment, and work-life balance policies. These strategies have been shown to improve job satisfaction, employee loyalty, and organizational commitment, thereby reducing turnover rates. Therefore, retention strategies should be implemented in an integrated and sustainable manner as part of hospital human resource management policies to retain competent healthcare professionals and improve the quality of healthcare services.